2016
DOI: 10.25241/stomaeduj.2016.3(1-2).art.2
|View full text |Cite
|
Sign up to set email alerts
|

Remineralizing potential of saliva on patients having dental erosions due to wine consumption

Abstract: The aim of the study is to assess the action of a remineralizing product (calcium-phosphatefluoride-based varnish) on the saliva remineralization capacity on patients having dental erosions caused by frequent wine consumption. Methodology: The study group was made up of 15 patients who are frequent wine consumers. Unstimulated saliva was collected on the same day and at the same hour for each patient. A total amount of 0.5 ml of unstimulated saliva was placed on a glass plate, dried for 30 minutes in a thermos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…These findings are similar with that ones from other studies [24,25]. Some authors suggested that relatively higher filler loading increases the stability of composite resin surface against low pH conditions [26][27][28]. However, still a not significantly increase in surface roughness of Micro Esthetic flow viscous samples when comparing to Gradia Direct LoFlo was noticed.…”
Section: Resultssupporting
confidence: 90%
“…These findings are similar with that ones from other studies [24,25]. Some authors suggested that relatively higher filler loading increases the stability of composite resin surface against low pH conditions [26][27][28]. However, still a not significantly increase in surface roughness of Micro Esthetic flow viscous samples when comparing to Gradia Direct LoFlo was noticed.…”
Section: Resultssupporting
confidence: 90%
“…Keywords: Casein-Phosphopeptide-Amorphous Calcium Phosphate Fluoride, Calcium Sodium Phosphosilicate, low-level laser therapy, desensitizing produced, Schiff Cold Air Sensitivity Scale Nowadays the prevalence of gingival recessions, abrasions, or erosions has increased due to the periodontal pathologies, excessive use of dental bleaching or professional oral hygiene, acid foods and beverages, bad oral hygiene habits, incorrect brushing techniques, or salivary disorders [1][2][3][4][5][6]. These disorders are frequently associated with cervical dentinal hypersensitivity, characterized by sharp pain of short duration occurring on exposure to the thermal, tactile, evaporative, osmotic, chemical stimuli, and it cannot be ascribed as other dental pathology [7].…”
mentioning
confidence: 99%
“…On the other hand, the hardness of the resin composite may be affected by acid attack [33,34]. Composite resins suffer a softening of the surface layer under the action of acids due to changes in the organic component [35].…”
Section: Resultsmentioning
confidence: 99%